2020
DOI: 10.1039/d0cp01474e
|View full text |Cite
|
Sign up to set email alerts
|

Graph convolutional neural networks with global attention for improved materials property prediction

Abstract: One of the major design issues in machine learning (ML) models for materials property prediction(MPP) is how to enable the models to learn property related physicochemical features. While many composition...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 17 publications
0
122
0
Order By: Relevance
“…Secondly, the MatErials Graph Network (MEGNet) created by Chen et al 144 reported a MAE of 0.38 eV on 36,720 inorganic solids which was later improved to 0.33 after transfer learning. A global attention graph neural network (GATGNN) by Louis et al 145 pushed the average error achieved to MAEs of 0.32 eV and 0.31 eV using Open Quantum Materials Database (OQMD) 142 and Materials Project 146 datasets. Lastly, a weighted average smooth overlap of atomic positions (SOAP) based regression model by Olsthoorn et al 147 reported a MAE of 0.39 eV.…”
Section: Machine Learning For Characterisation Of Conductive Mofsmentioning
confidence: 99%
“…Secondly, the MatErials Graph Network (MEGNet) created by Chen et al 144 reported a MAE of 0.38 eV on 36,720 inorganic solids which was later improved to 0.33 after transfer learning. A global attention graph neural network (GATGNN) by Louis et al 145 pushed the average error achieved to MAEs of 0.32 eV and 0.31 eV using Open Quantum Materials Database (OQMD) 142 and Materials Project 146 datasets. Lastly, a weighted average smooth overlap of atomic positions (SOAP) based regression model by Olsthoorn et al 147 reported a MAE of 0.39 eV.…”
Section: Machine Learning For Characterisation Of Conductive Mofsmentioning
confidence: 99%
“…(i) DTC [32]: a rumor detection method that uses decision tree classifiers based on various handcrafted features to obtain information credibility (ii) SVM-TS [33]: a linear SVM classifier that uses handcrafted features to construct a time series model (iii) GRU [34]: a RNN-based model that learns temporal linguistic patterns from user comments (iv) cPTK [35]: a SVM classifier based on propagation tree kernels is proposed based on the propagation structure of rumors (v) RvNN [36]: a rumor detection method based on the tree recurrent neural network with GRU units, which learns rumor representation by the propagation structure (vi) PPC_RNN+CNN [37]: a rumor detection model combining RNN and CNN, which learns rumor representation by the user's features in the rumor propagation path (vii) GAT_GNN [38]: constructs a generalized network rumor detection model based on the GAT and GNN layers using a bidirectional propagation structure For a fair comparison, we randomly divide the dataset into 5 parts and perform a 5-fold cross-test to obtain more stable results. On this dataset, this paper evaluates the accuracy (Acc.)…”
Section: Contrasting Modelsmentioning
confidence: 99%
“…[15][16][17][18] These concepts are increasingly being adapted for solid state materials, often involving materials representations that combine properties of the constituent elements with structural features. [19][20][21][22][23][24][25][26][27][28] While these approaches are being deployed to good effect, they are not applicable in the common scenario of experimental materials science wherein a given material is composed of a mixture of phases, or even more so when no knowledge of the phases is available. In exploratory research for materials with specific properties, measurement and interpretation of composition and property data are often far less expensive than measurement and interpretation of structural data.…”
Section: Introductionmentioning
confidence: 99%